21+4b+9b-10=22b+17-9b-6

Simple and best practice solution for 21+4b+9b-10=22b+17-9b-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21+4b+9b-10=22b+17-9b-6 equation:



21+4b+9b-10=22b+17-9b-6
We move all terms to the left:
21+4b+9b-10-(22b+17-9b-6)=0
We add all the numbers together, and all the variables
4b+9b-(13b+11)+21-10=0
We add all the numbers together, and all the variables
13b-(13b+11)+11=0
We get rid of parentheses
13b-13b-11+11=0
We add all the numbers together, and all the variables
=0
b=0/1
b=0

See similar equations:

| 2/3x-7=1/4x+12 | | 2/4(4x-5)+8=1/9(x+4) | | x²+3x+14=0 | | 2.4z+2.4z-6.5=0.7 | | -5/3x+2/3-1/3x+1=0 | | 2z+41/2=6 | | 22x+2-17(2x-1)+1=0 | | 16d+23=14(d−20 | | 22x+1-15(2x-1)-8=0 | | 18x=-13 | | 346=0.00012x^2+200 | | 4x-49=50-5x | | (3*x)=x+4 | | 5x-1=9x+11 | | -2+7K=5t-56 | | (6x-8)(2x+7)=0 | | x/2-3x/4+5x/6=220 | | 2x+7(x-3)=33 | | (1)/(12)(6y-1)+(2)/(3)=(1)/(18)(3-18y)+(5)/(6) | | -1x+12=4-2x+7 | | 2^x+1+4^x-1=96 | | 20h-12=24h+14 | | 6(y+2)—4=-10 | | 8(4u-1)-12u=11/ | | 0.6x=1.56 | | y+4=-y-6 | | 7x-3x+7=3(×-4)+20 | | -2z+20=-9z+29 | | 5+7x=-12+7x | | 1+x=1.05 | | 1.06g-3=0.17 | | 5+7x=7x–12 |

Equations solver categories